Comparison of Anterior Cervical Discectomy and Fusion With a Stand-Alone Interbody Cage Versus a Conventional Cage-Plate Technique: A Systematic Review and Meta-Analysis. Issue 4 (June 2019) - Cheung, Zoe B.; Gidumal, Sunder; White, Samuel; Shin, John; Phan, Kevin; Osman, Nebiyu; Bronheim, Rachel; Vargas, Luilly; Kim, Jun S.; Cho, Samuel K.
Study Design: Systematic review and meta-analysis. Objective: Compare the clinical and radiographic outcomes of anterior cervical discectomy and fusion (ACDF) with a stand-alone interbody cage versus a conventional cage and anterior cervical plate technique. Methods: A systematic Medline search was conducted using PubMed, EMBASE, and Cochrane Library Database of Systematic Reviews. Search terms included "anterior cervical discectomy and fusion, " "cage, " and "bone plates, " or variations thereof. Only studies involving a direct comparison of ACDF with a stand-alone cage versus a cage and plate were included. From the selected studies, we extracted data on patient demographics, comorbidities, surgical risk factors, and pre- and postoperative radiographic findings. A meta-analysis was performed on all outcome measures. The quality of each study was assessed using the Downs and Black checklist. Results: Nineteen studies met the inclusion and exclusion criteria. Patients who underwent ACDF with a cage-only technique had significantly lower rates of postoperative dysphagia and adjacent segment disease compared with patients who underwent ACDF with a cage-plate technique. However, patients who underwent ACDF with a cage-plate technique had better radiographic outcomes with significantly less subsidence and better restoration of cervical lordosis. There were no other significant differences in outcomes or postoperative complications. Conclusions: ACDF with a cage-only technique appears to have better clinical outcomes than the cage-plate technique, despite radiographic findings of increased rates of subsidence and less restoration of cervical lordosis. Future randomized controlled trials with longer term follow-up are needed to confirm the findings of this meta-analysis.